The Biotic and Abiotic Carbon Monoxide Formation During Aerobic Co-digestion of Dairy Cattle Manure With Green Waste and Sawdust - Stegenta-Dąbrowska, Sylwia; Drabczyński, Grzegorz; Sobieraj, Karolina; Koziel, Jacek A.; Białowiec, Andrzej (Frontiers in Bioengineering and Biotechnology, 2019)
Carbon monoxide (CO), an air pollutant and a toxic gas to humans, can be generated during aerobic digestion of organic waste. CO is produced due to thermochemical processes, and also produced or consumed by cohorts of methanogenic, acetogenic or sulfate-reducing bacteria. The exact mechanisms of biotic and abiotic formation of CO in aerobic digestion (particularly the effects of process temperature) are still not known. This study aimed to determine the temporal variation in CO concentrations during the aerobic digestion as a function of process temperature and activity of microorganisms. All experiments were conducted in controlled temperature reactors using homogeneous materials. The lab-scale tests with sterilized and non-sterilized mix of green waste, dairy cattle manure, sawdust (1:1:1 mass ratio) were carried out for one week at 10, 25, 30, 37, 40, 50, 60, 70 °C to elucidate the biotic vs. abiotic effect. Gas concentrations of CO, O2, and CO2 inside the reactor were measured every 12 h. The CO concentrations observed for up to 30 °C did not exceed 100 ppm v/v. For 50 and 60 °C, significantly (p<0.05) higher CO concentrations, reaching almost 600 ppm v/v, were observed. The regression analyses showed in both cases (sterile and non-sterile) a statistically significant effect (p<0.05) of temperature on CO concentration, confirming that the increase in temperature causes an increase in CO concentration. The remaining factors (time, O2, and CO2 content) were not statistically significant (p>0.05). A new polynomial model describing the effect of temperature, O2, and CO2 concentration on CO production during aerobic digestion of organic waste was formulated. It has been found that the proposed model for sterile variant had a better fit (R2 = 0.86) compared with non-sterile (R2 = 0.71). The model predicts CO emissions and could be considered for composting process optimization. The developed model could be further developed and useful for ambient air quality and occupational exposure to CO.